(untitled) - American Bible Society (United States of America, 2009)
What does the Bible tell us about the reality of miracles and angels? This book explores many Old and New Testament accounts and events that lie beyond our understanding and are thus described as supernatural. It also invites readers to explore the events as the Bible represents them and to discover the meaning they may hold for contemporary life.
Keywords: Demonology -- Miscellanea